A Broadband Dipole Antenna Implemented with Solar Cell - Ali, Ahmed; Wang, Heesu; Park, Ikmo (2023 International Workshop on Antenna Technology, iWAT 2023, 2023)
This paper presents a broadband fat dipole antenna made from a solar cell for dual functions of wireless communication and energy harvesting. For this purpose, the dipole elements of the antenna were made from a copper- indium-gallium-selenide-based solar cell; hence no extra structure was used for the antenna. This approach resulted in a very low-profile and simple solar cell antenna structure. A coaxial cable that was connected to the dipole elements was used for feeding. The antenna and the solar cell were made to operate independently of each other using RF decoupler circuits. The gap between the dipole elements was minimized to achieve a high form factor. The proposed solar cell integrated antenna has a broad impedance bandwidth of 94.2%, ranging from 2 GHz to 5.56 GHz. Moreover, the whole structure has a very compact size of 52.5 mm × 25 mm × 0.571 mm (0.66 λ 0 × 0.31 λ 0 × 0.0071 λ 0 at 3.78 GHz), with a form factor of 95.23% and optical transparency of 100%.
Keywords: Broad-band antenna; Dual function; Fat dipole antennas; Form factors; Gallium selenides; Integrated antennas; Low-profile; Solar cell integrated antenna; Wireless communications; Wireless energy; broadband antenna; dipole antenna; solar cell integrated antenna